Excessive endoplasmic reticulum stress drives aberrant mouse trophoblast differentiation and placental development leading to pregnancy loss. (19th August 2021) - Capatina, Nadejda; Hemberger, Myriam; Burton, Graham J.; Watson, Erica D.; Yung, Hong Wa
Abstract : Key points: Endoplasmic reticulum (ER) stress promotes placental dysmorphogenesis and is associated with poor pregnancy outcomes. We show that unfolded protein response signalling pathways located in the ER drive differentiation of mouse trophoblast stem cells into trophoblast subtypes involved in development of the placental labyrinth zone and trophoblast invasion. In a mouse model of chronic ER stress ( Eif2s1 tm1RjK ), higher ER stress in homozygous blastocysts is accompanied by reduced trophectoderm cell number and developmental delay and also is associated with an increased incidence of early pregnancy loss. Administration of the chemical chaperone, tauroursodeoxycholic acid, to Eif2s1 +/ tm1RjK heterozygous females during pregnancy alleviated ER stress in the mutant placenta, restored normal trophoblast populations and reduced the frequency of early pregnancy loss. Our results suggest that alleviation of intrauterine ER stress could provide a potential therapeutic target to improve pregnancy outcome in women with pre‐gestational metabolic or gynaecological conditions. Abstract: Women with pre‐gestational health conditions (e.g. obesity, diabetes) or gynaecological problems (e.g. endometriosis) are at increased risk of adverse pregnancy outcomes including miscarriage, pre‐eclampsia and fetal growth restriction. Increasing evidence suggests that unfavourable intrauterine conditions leading to poor implantation and/or defective placentation are a possible causative factor. The endoplasmic reticulum (ER) unfolded protein response (UPR ER ) signalling pathways are a convergence point of various physiological stress stimuli that can be triggered by an unfavourable intrauterine environment. Therefore, we explored the impact of ER stress on mouse trophoblast differentiation in vitro, mouse blastocyst formation and early placenta development in the Eif2s1 tm1RjK mutant mouse model of chronic ER stress. Chemically‐manipulated ER stress or activation of UPR ER pathways in a mouse trophoblast stem cell line promoted lineage‐specific differentiation. Co‐treatment with specific UPR ER pathway inhibitors rescued this effect. Although the inner cell mass was unaffected, the trophectoderm of homozygous Eif2s1 tm1RjK blastocysts exhibited ER stress associated with a reduced cell number. Furthermore, one‐third of Eif2s1 tm1RjK homozygous blastocysts exhibited severe developmental defects. We have previously reported a reduced trophoblast population and premature trophoblast differentiation in Eif2s1 tm1RjK homozygous placentas at mid‐gestation. Here, we demonstrate that treatment of Eif2s1 +/tm1RjK heterozygous pregnant females with the chemical chaperone tauroursodeoxycholic acid alleviated ER stress, restored the trophoblast population and reduced the frequency of embryonic lethality. Our data suggest that therapeutic targeting of ER stress may improve pregnancy outcome in women with pre‐gestational metabolic or gynaecological conditions. Key points: Endoplasmic reticulum (ER) stress promotes placental dysmorphogenesis and is associated with poor pregnancy outcomes. We show that unfolded protein response signalling pathways located in the ER drive differentiation of mouse trophoblast stem cells into trophoblast subtypes involved in development of the placental labyrinth zone and trophoblast invasion. In a mouse model of chronic ER stress ( Eif2s1 tm1RjK ), higher ER stress in homozygous blastocysts is accompanied by reduced trophectoderm cell number and developmental delay and also is associated with an increased incidence of early pregnancy loss. Administration of the chemical chaperone, tauroursodeoxycholic acid, to Eif2s1 +/ tm1RjK heterozygous females during pregnancy alleviated ER stress in the mutant placenta, restored normal trophoblast populations and reduced the frequency of early pregnancy loss. Our results suggest that alleviation of intrauterine ER stress could provide a potential therapeutic target to improve pregnancy outcome in women with pre‐gestational metabolic or gynaecological conditions.